Investigation of electrical properties with medium and heavy Brazilian crude oils by electrochemical impedance spectroscopy. (1st April 2019) - Rocha, John W.S.; Vicente, Maristela A.; Melo, Breno N.; Marques, Maria de Lourdes S.P.; Guimarães, Regina C.L.; Sad, Cristina M.S.; Castro, Eustáquio V.R.; Santos, Maria F.P.
Graphical abstract: Highlights: Investigation of electrical conductivity and dielectric constant of two oils. The conductivity and dielectric behavior are mainly controlled by polars content. Viscosity of a cut/oil blend can be determined by dielectric constant measurements. Viscosity of a W/O emulsion can be determined by dielectric constant measurements. Abstract: Petroleum and petroleum products characterization are vital for decision-making in the oil industry. Electrical properties have been used for quality, safety control, indirect characterization and investigation of some physicochemical properties of petroleum and by-products. In this study, a heavy and a medium oil, labeled as alpha and beta, respectively, their distillation products and water-in-oil (W/O) emulsions were characterized by impedance spectroscopy to obtain electrical conductivity and dielectric constant at 30 and 50 °C. The results were used to propose one among many ways in which electrical properties can be used to predict other non-electrical physical properties in the field. We obtained kerosene cut (KC), diesel cut (diesel) and atmospheric residue (RAT) after distillation of the oils. The blends KC/oil, diesel/oil and KC/RAT were synthesized to investigate the effect of viscosity increase and addition of polar compounds to the conductivity and dielectric constant of these cuts. We synthesized W/O emulsions containing 10, 30 and 50% w/w of saline water. The Nyquist diagrams for the oil samples, cuts and blends presented only a single semicircle. For emulsions, two semicircles were observed, one attributed to the oil phase and the other to the emulsion phase. It was observed that an increase in temperature was followed by an increase in electrical conductivity and a decrease in dielectric constant for all samples. The highest values of electrical conductivity and dielectric constant were observed for the alpha oil, which has higher viscosity and polar compounds than beta oil. For KC, diesel and RAT cuts, it was observed that electrical conductivity decreases and the dielectric constant increases for higher boiling range cuts (KC < diesel < RAT). Concerning the blends, incorporation of oil or RAT into the KC or diesel was followed by an increase in electrical conductivity up to a maximum at a concentration of 25% w/w oil or RAT, then the conductivity drops. It was observed that the dielectric constant increases linearly with the addition of oil or RAT and that it can be used to infer the viscosity of these blends by plotting ln (kinematic viscosity) as a function of dielectric constant. Water incorporation to the oils was followed by a decrease in electrical conductivity and a linear increase in the dielectric constant for both oils. This last result implies that one can predict emulsions viscosity by using the dielectric constant results of these emulsions.